2009
DOI: 10.1186/1471-2180-9-161
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of bacterial pathogens using a PCR- and microarray-based assay

Abstract: BackgroundDuring the course of a bacterial infection, the rapid identification of the causative agent(s) is necessary for the determination of effective treatment options. We have developed a method based on a modified broad-range PCR and an oligonucleotide microarray for the simultaneous detection and identification of 12 bacterial pathogens at the species level. The broad-range PCR primer mixture was designed using conserved regions of the bacterial topoisomerase genes gyrB and parE. The primer design allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 28 publications
1
71
0
5
Order By: Relevance
“…The assay is easy to process, reducing the risk of human error and providing high throughput and reliability for the routine laboratory diagnosis. 74,76,77 The main strength of the test is that it offers essential information for the treatment of septic patients 18 hours faster than traditional methods. Several papers have been presented indicating a high sensitivity and specificity (95% and 99%, respectively), although a lower diagnostic sensitivity (62%) has also been observed, nevertheless in a previous study a significantly lower diagnostic sensitivity (62%) was observed.…”
Section: Prove-it™ Sepsismentioning
confidence: 99%
“…The assay is easy to process, reducing the risk of human error and providing high throughput and reliability for the routine laboratory diagnosis. 74,76,77 The main strength of the test is that it offers essential information for the treatment of septic patients 18 hours faster than traditional methods. Several papers have been presented indicating a high sensitivity and specificity (95% and 99%, respectively), although a lower diagnostic sensitivity (62%) has also been observed, nevertheless in a previous study a significantly lower diagnostic sensitivity (62%) was observed.…”
Section: Prove-it™ Sepsismentioning
confidence: 99%
“…Also, it indicates that there were bands in lane number 3 (cDNA amplified with primer S4F, S4R), which referred to the presence of a single band with a molecular weight of (324bp); this reveals that the microorganism which caused the infection was belonged to S. aureus keratitis. Finally, lane numbers 4,5 showed no bands when the cDNA was amplified with (PA-SS-F, PA-SS-R) (9Y, 9Z) primers for P. aeruginosa and S. pneumonie respectively. The specimens gave a positive result in the second set of the PCR method (using the universal fungal primer) when has been amplified by the C. albicans species specific primer.…”
Section: Isolation and Identification Of Microbial Keratitis Causativmentioning
confidence: 99%
“…In such methods, the pathogen is simultaneously detected and identified, which results in more rapid diagnoses than those obtained by conventional culturing methods and obviates the need for additional culture tests. Rapid diagnostics can also reduce the use of antimicrobial agents in addition to allowing a faster switch to the most optimum treatment, thus reducing both sideeffects and costs [4].…”
Section: Introductionmentioning
confidence: 99%
“…123,124 The modified version of the assay used 10μL PCR product instead of using the standard volume of 3μL PCR product for hybridization, though all other steps were followed as stated in the protocol.…”
Section: Assessment Of Illnessmentioning
confidence: 99%
“…123 Analysis by Proveit™ Advisor software includes simultaneous identification of bacterial targets and evaluation of the control probes included in the array. Results were detected by signals from the hybridization of PCR products with target specific oligonucleotides on the array.…”
Section: Microarray Scanning and Analysismentioning
confidence: 99%